Investigating the factors affecting the speaking anxiety among ESL secondary students: Insights from a Malaysian secondary school - Sharon Anthony Lai, Anthony (2023)
In Malaysia, there was a growing need for widespread English learning due to its frequent use in everyday activities. It was considered crucial in education since Malaysia was among the few globally where English was a formal second language. Among English skills, speaking holds particular importance in both formal and informal daily situations. Researchers have emphasized enhancing speaking skills for better interaction, crucial alongside other abilities. Thus, this study aims to determine the level of secondary school students’ English speaking anxiety and identify the factors that affect their speaking anxiety. This mixed-method study was conducted among a sample of 200 participants from a public secondary school in Perak. All participants were aged 16 years old and 17 years old. The instrument used in this study were the adapted version of Horwitz Foreign Language Classroom Anxiety Scale (FLCAS) and a semi-structured interview. The findings found that there was a significant relationship between students’ English test results and their English speaking anxiety. In addition, this study also discovered the factors that were causing the students’ fear of speaking in English. This study provided further insights for future studies to explore other potential factors that could lead to students’ English speaking anxiety among students in schools or even in universities. Furthermore, this study was also beneficial for educational stakeholders, including teachers and policymakers responsible for designing and improving the syllabus.